Optimalisasi Model ARCS dalam Pembelajaran Tematik Untuk Meningkatkan Motivasi Belajar Peserta Didik di MI At-Taqwa Bondowoso - Sinta Yulis Pratiwi (EDUCARE: Journal of Primary Education, 2021)
This study aims to explain the optimization of the ARCS learning model as an effort to increase the learning motivation of students, especially in thematic learning at MI At-Taqwa Bondowoso. The method used is qualitative with a descriptive qualitative approach, while the type of research used in this research is field research. The data collection techniques used interviews, observation, and documentation. Data analysis used was condensation, data presentation, and verification. And the validity of the data uses triangulation of sources and techniques. The results of this study indicate (1) Thematic Learning Problems at MI At-Taqwa Bondowoso, namely: Teachers are less biased in utilizing learning media, so that the only sources used are textbooks, classroom learning is only centered in the teacher, the students' lack of interest in the learning process, so that students do not pay attention to the teacher who teaches. (2) The application of the ARCS model in thematic learning at MI At-Taqwa Bondowoso, namely: The implementation of the ARCS model was carried out by teachers with several methods and strategies such as modeling the way strategy and also contextual teaching and learning, ARCS Model as an alternative solution in learning for increasing students 'learning motivation is able to stimulate students' enthusiasm in thematic learning. Keywords: ARCS Model; Thematic Learning; Motivation to Learn Penelitian ini bertujuan untuk menjelaskan optimalisasi model pembelajaran ARCS sebagai upaya meningkatkan motivasi belajar peserta didik khususnya dalam pembelajaranTematik di MI At-Taqwa Bondowoso. Metode yang digunakan adalah kualitatif dengan pendekatan kualitatif deskriptif, sedangkan jenis penelitian yang digunakan dalam penelitian ini adalah penelitian lapangan (field research). Adapun teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Analisis data yang digunakan yakni kondensasi, penyajian data, dan verifikasi. Dan keabsahan datanya menggunakan triangulasi sumber dan teknik. Hasil penelitian ini menunjukkan (1) Problematika Pembelajaran Tematik di MI At-Taqwa Bondowoso, yaitu: Guru kurang biasa memanfaatkan media pembelajaran, sehingga sumber yang dipakai hanya buku ajar saja, Pembelajaran di kelas hanya berpusat pada guru, Kurangnya ketertarikan peserta didik dalam proses pembelajaran, sehingga peserta didik tidak memperhatikan guru yang mengajar. (2) Penerapan model ARCS dalam pembelajaran tematik di MI At-Taqwa Bondowoso, yaitu: Penerapan model ARCS dilakukan oleh para guru dengan beberapa metode dan strategi seperti strategi modeling the way dan juga contextual teaching and learning, Model ARCS sebaga solusi altenatif dalam pembelajaran untuk meningkatakn motivasi belajar peserta didik mampu merangsang semangat peserta didik dalam pembelajaran tematik. Kata Kunci: Model ARCS; Pembelajaran Tematik; Motivasi Belajar